Hovering control of submarine based on L1 adaptive theory via ballast tanks. (22nd August 2017) - Chen, Ying; Wang, Guanxue; Xu, Guohua; Zhang, Wei; Wang, Wenjin
This article proposed a novel method for submarine hovering control implement by ballast tanks based on L1 adaptive theory. The ballast tanks are able to provide submerge/emerge force by let in/out ballast tank water, and therefore adjust submarine position and altitude when low-speed maneuver largely limits rudder effect. After formulate and analysis models of ballast tanks as well as submarine dynamic, control scheme is determined as cascaded controller system. L1 adaptive theory is adopted for outer loop control, to deal with the nonlinearity and uncertainties of model, as well as environmental disturbance in hovering condition for the first time. Robustness of control system is tested through simulations based on Simscape. Large impact force is exerted on submarine to simulate missile launching and test restoring ability of ballast tanks control. Simulation results demonstrated that the submarine is able to maneuver and response precisely, despite of sudden impact.